(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Fetoplacental insufficiency (FPI) is a complex of symptoms caused by various disorders of both the placenta and the fetus due to various diseases and obstetric complications. The variety of manifestations of FPN, the frequency and severity of complications for the pregnant woman and the fetus, the predominant violation of one or another function of the placenta depend on the duration of pregnancy, the strength, duration and nature of the impact of the injury. factors, as well as the degree of expression of the compensatory and adaptive abilities of the "mother-placenta-fetus" system at the stage of development of the fetus and placenta.